A review of diet standardization and bolus rheology in the management of dysphagia. Issue 3 (June 2016) - Hanson, Ben
Abstract : Purpose of review: Texture modification is a widespread practice as a strategy for the management of dysphagia and can be very effective in individual cases. However, it is often performed in a qualitative, subjective manner and practices vary internationally according to multiple sets of national guidelines. This article aims to identify best practice by reviewing the theory and practice of texture modification, focussing on recent advances. Recent findings: Instrumental assessment of texture modification in vivo is challenging, and studies including rheology and perception have indicated that fluid viscosity is only one of many factors affecting texture modification in practice. Systematic reviews have identified a historical lack of high-quality clinical evidence, but recent controlled studies are beginning to identify positive and negative aspects of thickened fluids. Research and practice to date have been limited by the lack of control and standardization of foods and drinks. However in 2015 a not-for-profit organization, the International Dysphagia Diet Standardisation Initiative, has published a framework for texture modification from thin liquids to solid foods based on all the existing documentation and guidance, and the – limited – available clinical evidence. Summary: Rheology exists in the lab; however, normal practice is often subjective or lacking control and standardization. In the near future, cohesion of practice and the availability of practical standardization tools may increase awareness and use of rheology.